Routine microscopy examination of faecal samples as a tool for detection of common gastrointestinal parasites: a preliminary report from two Hungarian farms - Khangembam, Rojesh; Czeglédi, Levente; Vass, Nóra (Acta Agraria Debreceniensis, 2023)
Gastrointestinal parasitism in ruminant animals is a cause of major economic loss incurred by the livestock industry. Regardless of the frequency of the adopted therapeutic and prophylactic deworming strategies, the parasitic burden in a farm should be assessed regularly. One of the most widely used techniques to do so is the microscopic faecal egg examination and faecal egg counting method. Despite the technique being almost a century old from its first adoption, the principle behind the newer techniques of faecal egg examination is the same. This technique is still being used in routine farm screening and monitoring gastrointestinal parasitic load and faecal egg count reduction testing to assess the anthelmintic efficacy of the drugs used. Thus, the tool remains a choice for preliminary screening for important parasites and the subsequent deworming strategy. Our study here was part of a larger survey on the treatment efficiency as well as a broad epidemiological study of the trichostrongyle parasites in Hungary. We present a preliminary report on the detection of common gastrointestinal parasites from two farms in Hungary, including a species-specific confirmatory microscopy for Haemonchus contortus eggs.